2022
DOI: 10.3390/ma15217439
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mixed Na2O/K2O on Chemical Durability and Spectral Properties of P2O5-Al2O3-BaO-K2O-Na2O-Nd2O3 Phosphate Glasses

Abstract: A series of 56P2O5-7.5Al2O3-5.9BaO-(28.56-x)K2O-xNa2O-1.51Nd2O3 phosphate glasses with different Na/(Na+K) ratios, which were specially designed for high-power laser application, were prepared by a high-temperature melting method. Except for the density, refractive index, glass transition temperature, and DC conductivity, the chemical durability and spectral properties, as emphasized by high-power and high-energy laser material, were further measured and analyzed. Regarding the chemical durability, the dissolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Lei et al demonstrated an average output power of 490 mW with a pulse duration of 324 fs using a rotary Nd: glass disk [19]. A novel Nd-doped phosphate glass, denoted as N51, has been successfully developed with enhanced thermal properties and an increased stimulated emission cross section [20,21]. Consequently, the N51-type Nd: glass holds promise for the advancement of high-power mode-locked lasers in a standard configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al demonstrated an average output power of 490 mW with a pulse duration of 324 fs using a rotary Nd: glass disk [19]. A novel Nd-doped phosphate glass, denoted as N51, has been successfully developed with enhanced thermal properties and an increased stimulated emission cross section [20,21]. Consequently, the N51-type Nd: glass holds promise for the advancement of high-power mode-locked lasers in a standard configuration.…”
Section: Introductionmentioning
confidence: 99%